2004
DOI: 10.1111/j.1360-2322.2004.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Selves: a Grounded Theory Account of Belonging to a Self‐advocacy Group for People with Intellectual Disabilities1

Abstract: Purpose  To explore the experience of belonging to a self‐advocacy group for people with intellectual disabilities, and how membership of such a group impacts on individual members. Methods  Eight people with intellectual disabilities, who belonged to a self‐advocacy group for at least 6 months, were interviewed about their experiences of membership. A grounded theory approach was used to generate and analyse the interview data. Results  A model of the impact of belonging to a self‐advocacy group for people wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 10 publications
2
64
0
1
Order By: Relevance
“…The need is further described as so vital that it underlies one's ability to survive, reproduce, defend or protect oneself from external threats (Baumeister and Leary 1995). Clearly, for the women who contributed to this study, a sense of belonging motivated them to form affirming social bonds with others in their social world; it connected the women to others, places and things and provided them with a sense of security (Hagerty et al 1992, Andersen andChen 2002) and status (Beart et al 2004), and it augmented their social integration and positively contributed to their physical, psychological, emotional and cognitive wellbeing (Lindgren 1990, Hagerty and Patusky 1995, Ghavami et al 2011. When the women's perception of the self corresponded with 247 Hagerty and Patusky (1995) devised The Sense of Belonging Instrument (SOBI), a 27 item self-report instrument designed to measure an individual's sense of belonging.…”
Section: Situating the Substantive Theory Within The Framework Of Extmentioning
confidence: 98%
“…The need is further described as so vital that it underlies one's ability to survive, reproduce, defend or protect oneself from external threats (Baumeister and Leary 1995). Clearly, for the women who contributed to this study, a sense of belonging motivated them to form affirming social bonds with others in their social world; it connected the women to others, places and things and provided them with a sense of security (Hagerty et al 1992, Andersen andChen 2002) and status (Beart et al 2004), and it augmented their social integration and positively contributed to their physical, psychological, emotional and cognitive wellbeing (Lindgren 1990, Hagerty and Patusky 1995, Ghavami et al 2011. When the women's perception of the self corresponded with 247 Hagerty and Patusky (1995) devised The Sense of Belonging Instrument (SOBI), a 27 item self-report instrument designed to measure an individual's sense of belonging.…”
Section: Situating the Substantive Theory Within The Framework Of Extmentioning
confidence: 98%
“…In three of the studies (Beart et al, 2004;Clifford, 2013;Gilmartin & Slevin, 2010), there was mention of possible sources of influence on the data, but the likely impact of the influences was not discussed. In three of the studies (Beart et al, 2004;Clifford, 2013;Gilmartin & Slevin, 2010), there was mention of possible sources of influence on the data, but the likely impact of the influences was not discussed.…”
Section: Quality Rating Of the Studiesmentioning
confidence: 99%
“…Beart, Hardy, and Buchan (2004) found that a self-advocacy group's development of a political consciousness heightened self-advocates' negative perceptions of their past. The history of marginalization of people with intellectual disabilities as an oppressed social class is central to the self-advocacy movement (Clifford 2013).…”
Section: Passionate Encountersmentioning
confidence: 99%
“…For example, an advocacy campaign that combats prejudice by raising political awareness about social injustice may decrease a person's sense of well-being as it draws attention to the injustices he or she experiences (Beart, Hardy, and Buchan 2004). In this way, communitarian ideals of inclusion -such as increasing happiness through facilitating a sense of belonging -may stall broader political goals.…”
Section: Disability and Society 721mentioning
confidence: 99%